Effect of growth hormone-release inhibiting hormone on hormones stimulating exocrine pancreatic secretion. - Konturek, S J (1976)
The nature and extent of growth hormone-release inhibiting hormone (GH-RIH, somatostatin)-induced inhibition of pancreatic secretion of bicarbonate and protein, an index of enzyme secretion, were studied by administration of exogenous secretin or cholecystokinin (CCK) and of a number of stimulants for endogenous release of these hormones in fasted pancreatic fistula dogs with and without an infusion of GH-RIH. The results of this study show that GH-RIH inhibits the pancreatic fluid and bicarbonate secretion induced by duodenal acidification and exogenous secretion. The kinetic analysis shows that the interaction between GH-RIH and secretin affecting pancreatic bicarbonate secretion possesses the characteristics of competitive inhibition. GH-RIH does not change the pancreatic protein response to exogenous CCK, but profoundly inhibits pancreatic response to a variety of the endogenous stimulants of CCK release, including duodenal perfusion of sodium oleate, amino acid mixture, or feeding of a peptone meal. We conclude that GH-RIH is a very potent inhibitor of the endogenous release of CCK from the intestinal mucosa and inhibits competitively the action of secretin but not CCK on the exocrine pancreatic secretion.